Stability and Degradation of Perovskite Electrocatalysts for Oxygen Evolution Reaction. (10th November 2016) - Bick, D.S.; Kindsmüller, A.; Staikov, G.; Gunkel, F.; Müller, D.; Schneller, T.; Waser, R.; Valov, I.
Abstract: Pr0.2 Ba0.8 CoO3-δ (PBCO) and Ba0.5 Sr0.5 Co0.5 Fe0.5 O3-δ (BSCF) perovskite thin film electrodes were used as model systems for testing degradation and stability during oxygen evolution reaction (OER) in alkaline water electrolysis. The catalyst films were prepared by chemical solution deposition (CSD) and are binder-free. Stepwise aging experiments illustrate a systematical approach to different degrees of degradation of the perovskites after defined testing cycles of cyclic voltammetry in application-near conditions. XPS and EDX characterization at each aging step enables a monitoring of the change in chemical composition during degradation. XPS analysis points to a change in the defect chemistry of PBCO during degradation. The influence of all monitored parameters on the overall electrode service lifetime is shown in a novel end of service life test (ESLT) at thin film perovskite electrodes of 100 nm thickness.